Unilateral Buccinator Flap for Lengthening of Short Palate. Issue 6 (September 2018) - Hassani, Mohammad-Esmaiil; Latifi, Noor-Ahmad; Karimi, Hamid; Khakzad, Mohammad
Abstract : Background: Velopharyngeal insufficiency is one of the most frequent complications after cleft palate repair. Purpose: To evaluate the results and complications of unilateral Buccinator flap (BMF) in velopharyngeal insufficiency. Materials and Methods: During 4 years the authors performed unilateral BMF in all short palates. Age, sex, demographic data, length of palate, cause of short palate, nasopharyngoscopy and videofluroscopy results, hyper nasality, nasal escape, nasal emission, nasal fluid leak, speech evaluation and results, outcome and complications of the treatment were surveyed before surgery and in 1, 3, 6 months after treatment. Results: The authors had 43 patients, 29 below 8 years old and 14 adults. Velopharyngeal gap was between 10 and 27 mm, mean 21 mm. Buccinator flap were measuring 15 to 19 mm in width and 32 to 56 mm in length. The operation time was 80 to 100 minutes, mean 86 minutes. Nasal emission, nasal escape, and nasal leak were treated in all patients. Hyper nasality was completely improved in all of the patients below 8 years old (29 patients) and in 10 patients of the adults (totally 39 patients, 90.6%). And it was improved significantly in other 4 patients (9.4%). The speech evaluation reported between 70% and 86% improvements. The lengthening of the palate was between 12 and 19 mm, mean 17 mm. The satisfaction of the patients was as 0% poor, 2.3% fair, 72.1% good, and 25.6% excellent. Conclusion: Unilateral BMF is reliable, promising, and safe flap for lengthening of short palate and it can lengthen the palate up to 19 mm. The time of surgery is very short compared with other methods. It is an anatomical treatment versus pharyngeal flap which is not an anatomical one. Speech improvement will achieve in 70% to 86% patients. Abstract : Supplemental Digital Content is available in the text